Polymorph phosphor SrSi2O2N2:Eu2+ optoelectronic properties for highly efficient LED: ab-initio calculations. (December 2017) - Azam, Sikander; Khan, Saleem Ayaz; Goumri-Said, Souraya
Graphical abstract: Polymorph LED Highlights: A doped europium polymorph based on phosphor, SrSi2 O2 N2, is investigated using DFT. Band gap was reduced from the parent SrSi2O2N2, 6.646 eV to 4.66 eV due to doping. Optical properties for radiation to explore the characteristics of various spectra. Possibility to explore the polymorph SrSi2 O2 N2 :Eu 2+ for LED devices. Abstract: A doped europium polymorph based on phosphor with a structure of SrSi2 O2 N2 was investigated using the density functional theory as implemented in the full potential linear augmented plane wave method. The exchange correlation was described within the generalized gradient approximation added to the optimized effective Hubbard parameter. The optoelectronic properties were reported to explore the possibility to use SrSi2 O2 N2 :Eu 2+ for light-emitting diodes (LED) devices. The electronic band gap was reduced from the parent SrSi2O2N2, 6.646 eV to 4.66 eV when europium was incorporated and it is a direct band gap. The densities of states have shown the role of europium and its f- orbitals in tuning the band gap. Optical properties, such as optical reflectivity, refractive index and electron energy loss, were deduced from the dielectric function for radiation up to 15 eV. The present calculations suggest clearly that SrSi2 O2 N2 :Eu 2 is a promising compound for LEDs devices.